2021
DOI: 10.1039/d0fo01764g
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds from an Algerian medicinal plant (Pallenis spinosa): simulated gastrointestinal digestion, characterization, and biological and enzymatic activities

Abstract: Pallenis spinosa is a medicinal plant which is used in folk medicine as curative or preventive remedies for various diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
3
3
1
Order By: Relevance
“…Interestingly, Izzo et al [38] have reported that red cabbage extract encapsulated in AR capsule after in vitro gastrointestinal digestion showed higher colon bioaccessibility when compared to the extract digested without a capsule. Similar results have been observed by Amrani-Allalou et al [39], who reported a strong decrease in TPC value during gastrointestinal digestion in non-encapsulated medicinal plant extracts compared to the same extracts containing in AR capsules. These outcomes show that the AR capsules are able to protect the polyphenol fraction from the gastric condition, protecting the chemical characteristics of the bioactive molecules.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, Izzo et al [38] have reported that red cabbage extract encapsulated in AR capsule after in vitro gastrointestinal digestion showed higher colon bioaccessibility when compared to the extract digested without a capsule. Similar results have been observed by Amrani-Allalou et al [39], who reported a strong decrease in TPC value during gastrointestinal digestion in non-encapsulated medicinal plant extracts compared to the same extracts containing in AR capsules. These outcomes show that the AR capsules are able to protect the polyphenol fraction from the gastric condition, protecting the chemical characteristics of the bioactive molecules.…”
Section: Discussionsupporting
confidence: 90%
“…These results align with prior studies that observed similar high polyphenol bioaccessibility in the colonic stage for water-based extracts enclosed in AcR capsules, such as fennel waste and red cabbage extracts [12,55]. Amrani-Allalou et al [56] also reported that plant extracts encapsulated in AcR capsules displayed notably higher TPC values following GiD processing compared to the same extracts examined without protective capsules.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Izzo et al [ 58 ] also demonstrated that red cabbage extract contained in ARC formulations showed higher colon bioaccessibility than the not-encapsulated extract. In this line, Amrani-Allalou et al [ 59 ] reported a higher TPC value after the GI process in plant extracts encapsulated in ARC compared to the same extracts tested without capsules.…”
Section: Discussionmentioning
confidence: 95%